Drug-efflux and target-site gene expression patterns in Haemonchus contortus larvae able to survive increasing concentrations of levamisole in vitro - Sarai, Ranbir S. (Elsevier, 2014)
While there is some evidence that changes in nicotinic acetylcholine receptor (nAChR) subunits confer resistance to levamisole in gastrointestinal helminth parasites, the exact nature of the resistance mechanism(s) is unclear. We utilised the presence of a resistant fraction within the Wallangra 2003 isolate of Haemonchus contortus larvae in order to subdivide the population into three subpopulations of larvae able to survive increasing concentrations of the drug. We then measured gene expression levels in the subpopulations and the larval population as a whole, focusing on genes encoding the subunit components of levamisole-sensitive receptors, genes encoding ancillary proteins involved in receptor assembly, and P-glycoprotein (P-gp) genes. The subpopulation surviving the lowest levamisole concentration showed increases of 1.5- to 3-fold in a number of P-gp genes (Hco-pgp-3, -4, -10, and -14) alongside unchanged receptor genes, compared to the whole Wallangra larval population. On the other hand, the subpopulation surviving the intermediate levamisole concentration showed an increase in only a single P-gp (Hco-pgp-14), alongside decreases in some receptor subunit (Hco-unc-63a) and ancillary protein genes (Hco-unc-50, Hco-ric-3.1 and 3.1). The subpopulation surviving the highest levamisole concentration showed further decreases in receptor subunit genes (Hco-unc-63a and Hco-unc-29 paralogs) as well as genes involved in receptor assembly (Hco-unc-74, Hco-unc-50, Hco-ric-3.1 and 3.1), alongside no increased P-gp gene levels. This suggests a biphasic pattern of drug resistance in the larvae of this worm isolate, in which a non-specific P-gp-mediated mechanism confers low levels of resistance, while higher level resistance is due to altered receptor subunit composition as a result of changes in both subunit composition and in the levels of proteins involved in receptor assembly.